Importance of comprehensive hip strengthening - Holcomb, W. R.; Miller, M. G.; Rubley, M. D. (Strength and Conditioning Journal, 2012)
Hip strength imbalances and instability are common in athletes and can lead to lower extremity injuries. This is largely due to popularity of resistance exercises that target hip extension with a lack of emphasis on exercises that focus on other hip movements. This challenge of comprehensive hip strengthening is addressed.